H Hubungan antara Kecerdasan Emosional dan Gaya Resolusi Konflik pada Pernikahan Kristen di wilayah Jabodetabek: The relationship between emotional intelligence components and conflict resolution styles in Christian marriage - Sanjaya, Yunita; Mailool, Elisabeth Lilis; Utami, Asriningrum (Universitas Brawijaya, 2024)
Marital conflict is the primary reason for marital divorce in Indonesia. A constructive conflict resolution style is required to maintain marital stability and quality. The present research examined the relationship between components of emotional intelligence (self-awareness, managing emotions, motivating oneself, empathy, and social skills) and conflict resolution styles among Christian married couples. The study included 205 respondents from Christian communities across a range of denominations. The results show that all components of emotional intelligence correlated positively with positive problem-solving styles and were inversely related to the conflict engagement style. The conflict withdrawal style was not associated with the managing emotions component but was inversely related to other components of emotional intelligence. The compliance style correlated negatively with the self-awareness component but not with the rest of the components of emotional intelligence. Research discussion focuses on the benefits of emotional intelligence in conflict resolution among married couples. Keywords: emotional intelligence, conflict resolution styles, Christian marriage, marital conflict